Post-stroke depression: different characteristics based on follow-up stage and gender–a cohort perspective study from Mainland China. (2nd November 2017) - Wang, Zixuan; Zhu, Meifang; Su, Zhaoping; Guan, Boyuan; Wang, Anxin; Wang, Yongjun; Zhang, Ning; Wang, Chunxue
Abstract: Background: Post-stroke depression (PSD) is a common and important comorbidity in patients after stroke. It negatively impacts stroke survivors' outcomes. Plenty of studies have investigated risk factors for PSD, especially sex differences. However, the results remain inconsistent. In this study, we explored the prevalence and risk factors for PSD both in the acute phase and the chronic phase of stroke, emphasizing on the impact of gender in PSD. Methods: About 1094 patients with first-ever ischemic stroke were included in the study. Patients were followed up, respectively, 2 weeks, 3 months, and 12 months after stroke. Data collected included demographic and stroke-related factors, and whether patients still suffer from PSD at each time points. T -test, chi-square test, and Wilcoxon rank-sum test were used to explore the group differences between patients with PSD and without PSD, and between female and male patients. Logistic regression was performed to investigate the risk factors for PSD both in the acute and the chronic stage of stroke. Results: The prevalence of PSD was 25.4, 17.6, and 12.4%, respectively 2 weeks, 3 months, and 12 months after stroke. Female patients had higher prevalence of PSD compared with male patients (31.4 vs. 22.4% 2 weeks after stroke; 20.05 vs. 16.22% 3 months after stroke; 15.04 vs. 11.05% 12 months after stroke). In the acute stage of stroke, female gender (OR 1.686 95%CI 1.155–2.462) and National Institutes of Health Stroke Scale (NIHSS) score (OR 1.118 95%CI 1.076–1.162) were independent risk factors for PSD. However, in the chronic stage of stroke, risk factors for PSD were different. At 3 months, NIHSS score (OR 1.082 95%CI 1.037–1.128), smoking (OR 1.772 95%CI 1.163–2.701), and frontal lobe lesion (OR 2.331 95%CI 1.472–3.692) were independent risk factors for PSD. On the other hand, education level (OR 0.693 95%CI 0.486–0.998) was a protective factor. About 12 months after stroke onset, NIHSS score (OR 1.113 95%CI 1.062–1.167) and living alone (OR 3.608 95%CI 1.538–8.466) were risk factors for PSD. Conclusion: PSD is common in stroke survivors, and female patients have higher prevalence of PSD. Risk factors for PSD in the acute phase are different from that in the chronic phase of stroke. Female gender is an independent risk factor for PSD in the acute stage of stroke. Smoking, frontal lobe lesion, and living alone are predictive factors for PSD in the chronic stage of stroke. NIHSS score is a risk factor for PSD both in the acute and in the chronic stage of stroke. Further studies are needed to understand the mechanisms underlying the elevated prevalence of PSD in female.